2016
DOI: 10.1080/02640414.2016.1215496
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bike-fit in the perception of comfort, fatigue and pain

Abstract: The aim of this study was to assess the influence of different bike positions on the perception of fatigue, pain and comfort. Twenty cyclists underwent three tests that involved cycling for 45 min at their individual 50% peak aerobic power output while adopting different positions on the bike. Participants performed the cycling tests adopting three positions defined by two parameters (knee flexion angle [20°, 30°, 40°] and trunk flexion angle [35°, 45°, 55°]) in random order. Angles were measured using a 2D mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 45 publications
3
36
0
2
Order By: Relevance
“… 21 , 22 One study 21 did not assess bicycle pedaling and was limited to clinical description of symptoms and imaging scan. Four studies 23 26 did not assess cyclists with injury or pain on the knees but assessed injury-related outcomes that could potentially explain the reason for why cyclists develop knee pain ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“… 21 , 22 One study 21 did not assess bicycle pedaling and was limited to clinical description of symptoms and imaging scan. Four studies 23 26 did not assess cyclists with injury or pain on the knees but assessed injury-related outcomes that could potentially explain the reason for why cyclists develop knee pain ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…While previous research has reported the frequency and type of cycling-related cycling [2,57], there less research related to the associated risk factors and prevention factors, both of which are fundamental the development of prevention programs that aim to reduce the incidence and severity of injuries [8]. Although studies have hypothesized that risk factors for cycling injuries include sex [2,9] and age [2], modifiable factors such as cycling profile or bicycle equipment [10–12] are also worth examining.…”
Section: Introductionmentioning
confidence: 99%
“…Perceived comfort during cycling can depend on bike components, cycling posture, and environmental factors (e.g. road conditions) [12,16]. Likewise, perceived pain may be associated by certain factors, such as the type of physical activities in which athletes participate [17].…”
Section: Introductionmentioning
confidence: 99%
“…6 This method involves determining knee joint flexion angles at the bottom of the crank cycle to attempt obtaining a knee angle close to 30–33°, in order to optimise comfort. 7…”
Section: Introductionmentioning
confidence: 99%